Exploring the Epidemic Spreading in a Multilayer Metapopulation Network by considering Individuals' Periodic Travelling. (21st April 2020) - Han, Dun; Shao, Qi; Li, Dandan
Abstract : The convenience of transportation brings the diversity of individuals' travelling modes; in this paper, we present an improved epidemic diffusion model in a multilayer metapopulation network. Firstly, we construct the metapopulation network with different travelling ways, and then, the epidemic spreading threshold is calculated by means of the mean-field method. Taking the periodicity of individuals' travelling into account, we further explore the epidemic diffusion model with individuals' periodic travelling and deduce the epidemic spreading threshold using the Perron–Frobenius theorem. Our results show that if all individuals in each area decide to move, the epidemic threshold can be effectively raised while each individual chooses an unbiased region to arrive. In addition, with the increase of individuals' mobility rate or regional heterogeneous infection coefficient, the fluctuation range of the density of infected becomes larger, while the fluctuation period is almost unchanged. However, the change of individuals' periodic motion could cause the change of the fluctuation period of infected density. We try to provide a new perspective for the research of metapopulation.